PENGARUH STRATEGI CUSTOMER BONDING TERHADAP LOYALITAS NASABAH PT. BANK NEGARA INDONESIA (PERSEO) Tbk (Studi pada Nasabah Taplus Bisnis Kantor Cabang Pekanbaru) - SM, DAMRI (Menara Ilmu, 2018)
The present research sought to find out the effect of each customer bonding process including awareness, identity, relationship, community and advocacy bonding on the customer loyalty. The data were collected using a questionnaire of 250 Business Taplus Customers chosen using purposive sampling technique. The data were analyzed using partial least square because normality, homogeneity and outlier assumptions were not met.The results showed that the customer bonding process reciprocally had positive and significant relationships in that awareness bonding affected identity bonding and identity bonding affected relationship bonding, the relationship bonding had an effect on community bonding, the community bonding had an effect on advocacy bonding. Whereas, the relationship between customer bonding and customer loyalty were only positive and significant at two levels, advocacy bonding and relationship bonding. While on the levels of awareness bonding, identity bonding and community bonding had a positive but insignificant affect on the customer loyalty.Various actions should be done in order to strengthen the customer bonding so that the customer loyalty could be increased. These included advertisements, promotional programs, and public corporate social responsibility, the content and renewal of website information, and customer-focused community. Key words: customer bonding, awareness bonding, identity bonding, relationship bonding, community bonding, advocacy bonding, customer loyalty, Bank BNI Pekanbaru